Identification and characterization of CHCHD1, AURKAIP1, and CRIF1 as new members of the mammalian mitochondrial ribosome - Koc, Emine C.; Cimen, Huseyin; Kumcuoglu, Beril; Abu, Nadiah; Akpinar, Gurler; Haque, Md E.; Spremulli, Linda L.; Koc, Hasan (Frontiers in Physiology, 2013)
Defects in mitochondrial ribosomal proteins (MRPs) cause various diseases in humans. Because of the essential role of MRPs in synthesizing the essential subunits of oxidative phosphorylation (OXPHOS) complexes, identifying all of the protein components involved in the mitochondrial translational machinery is critical. Initially, we identified 79 MRPs; however, identifying MRPs with no clear homologs in bacteria and yeast mitochondria was challenging, due to limited availability of expressed sequence tags (ESTs) in the databases available at that time. With the improvement in genome sequencing and increased sensitivity of mass spectrometry (MS)-based technologies, we have established that four previously known proteins as MRPs and have confirmed the identification of ICT1 (MRP58) as a ribosomal protein. The newly identified MRPs are MRPS37 (Coiled-coil-helix-coiled-coil-helix domain containing protein 1-CHCHD1), MRPS38 (Aurora kinase A interacting protein1, AURKAIP1), MRPS39 (Pentatricopeptide repeat-containing protein 3, PTCD3), in the small subunit and MRPL59 (CR-6 interacting factor 1, CRIF1) in the large subunit. Furthermore, we have demonstrated the essential roles of CHCHD1, AURKAIP1, and CRIF1in mitochondrial protein synthesis by siRNA knock-down studies, which had significant effects on the expression of mitochondrially encoded proteins.